The effect of game-based math education on creativity, social skills and academic self-efficacy of preschool students through Flipped Learning, and model presentation - Alireza Malekshahi,; Abdollah Ali Esmaeeli,; Ali Asghar Shojaee, (International Journal of Psychosocial Rehabilitation, 2020)
The present study aimed at the effect of game-based mathematics education on creativity, social skills and academic self-efficacy of preschool students through Flipped learning. The research method was quasi-experimental and applied in terms of purpose. The research plan is pre-test and post-test with the control group. The statistical population consisted of elementary school boys and girls. Among them, a sample with a volume of 40 people was selected by multi-stage cluster random sampling and placed in two experimental and control groups in the form of two classrooms. In both groups, a pre-test was performed, and after the pre-test, the Starmath training was performed for the training group, but the control group did not receive any training, and then the post-test was performed. In this study, the tools of Torrance Form B (1998) and the social skills of Tak and Trend (2014) and the academic self-efficacy of Jings and Morgan (1999) were used. Their reliability with Cronbach's alpha was 0.802, 0.848 and 0.706, respectively. The resulting data were described and analyzed with descriptive and inferential statistics (One Way ANOVA and Paired-Sample T Test). In order to study the research hypotheses; The data were transferred to the raw data pages of the software (Spss 20) for analysis and to the structural equations to SmartPLS software for analysis. Findings from statistical analyzes showed that the effect of Starmath on students' creativity, social skills and academic self-efficacy was positive and significant. Also, the causal model designed in the study was adapted based on the structural equation model. The goodness index of fit and root was the mean of the residual mean in the latent variable model RMSEA = 0.074. Therefore, the model has a favorable fit and thus the structural equation model of game-based mathematics education has been effective on creativity, social skills and academic self-efficacy of preschool students through Flipped learning. Therefore, with Starmath training, we can increase the skills and abilities of creativity and social skills in learning mathematical concepts and children's self-efficacy.